IMPLEMENTASI PENJAMINAN MUTU DI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS SEBELAS MARET - Murwaningsih, Tri (Jurnal Inovasi Pendidikan, 2009)
Responding to the global challenge, education is expected to make an effort of service quality assurance of education (Quality Assurance) and produce graduate students who fulfill the standard. Implementation of quality assurance by higher education at university will be able to give the best academic service for the students. The result of the research is to inform that there are three study programs that have implemented quality assurance: Economics Education, Geography education and Mechanical Engineering Education. However, there are 10 steps in quality assurance which have not been already implemented. Reward and punishment have not been implemented for the lecturer yet.